2014
DOI: 10.1111/anae.12906
|View full text |Cite
|
Sign up to set email alerts
|

The laboratory performance of the enFLOW®, buddy liteand ThermoSens®fluid warmers

Abstract: SummaryWe measured heating of isotonic saline by three fluid warmers in six experiments: saline at 5°C or 20°C delivered at 30, 50 or 100 ml.min À1 . At the three flow rates, the enFLOW The results for saline at 20°C were similar. The enFLOW system heated saline above 36°C faster than the ThermoSens system, whereas the buddy lite often failed to achieve 36°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…This observation may have aligned with one of the periods of absent warming, resulting in the impression that the device had shut down, and it is possible that heating may have been again observed had the experiment continued for a longer period of time. Other authors have also noted poorer performance of the Buddy Lite compared with other warmers at flow rates of 100 ml.min −1 or greater . We believe our study is the first to evaluate the comparative performance of the Hypotherm X LG or the °M Warmer devices.…”
Section: Discussionmentioning
confidence: 70%
“…This observation may have aligned with one of the periods of absent warming, resulting in the impression that the device had shut down, and it is possible that heating may have been again observed had the experiment continued for a longer period of time. Other authors have also noted poorer performance of the Buddy Lite compared with other warmers at flow rates of 100 ml.min −1 or greater . We believe our study is the first to evaluate the comparative performance of the Hypotherm X LG or the °M Warmer devices.…”
Section: Discussionmentioning
confidence: 70%
“…The effectiveness of ThermoSens® and Ranger™ have been studied at different flow rates [571316]. However, there were no studies investigating whether ThermoSens® and Ranger™ can effectively deliver warm fluid at low and moderate flow rates (below 1000 ml/h) in clinical and laboratory conditions, except for Jung's report using Ranger™ [7].…”
Section: Discussionmentioning
confidence: 99%
“…This can be aggravated by massive volume resuscitation with room-temperature crystalloid fluid and refrigerated blood transfusions [2]. Many laboratory and clinical studies at moderate and high flow rates (above 1,000 ml/h) have shown that fluid warmers can effectively heat intravenous fluids, and prevent hypothermia [3456]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are data supporting the warming performance of the enFlow (Vyaire Medical, Chicago, IL, USA), with crystalloids , there are no data on its impact on pressures when used in‐line with an extracorporeal circuit. In this in vitro experimentation we aimed at studying this blood warmer to ensure that its smaller size does not increase the resistance beyond a tolerable clinical threshold and aimed at evaluating its warming performance with blood at high flow.…”
mentioning
confidence: 99%